Response Surface Methodology of Glutamine, Asparagine and 2,4-Dichlorophenoxyacetic Acid for Agave americana L. Embryo Number and their Optimization in a RITA® Automatic Bioreactor System - Gutiérrez Oliva, Vicente Federico Federico; Castro, Arias-Castro; Herrera, Irving; Mendiola, Martha Alicia Rodríguez; Miceli, Federico Antonio Gutiérrez (International Journal of Biotechnology for Wellness Industries, 2014)
Response surface methodology was used to investigate the effect of different concentrations of 2,4-dicholorophenoxyacetic acid (2,4-D), asparagine and glutamine on a number of embryos from callus of Agave americana L generated with 0.5mg/L of 2,4-D, treatments obtained according to an experimental design with response surface Box-Behnken with three repetitions at the central point with 0, 1 and 2 mg L-1 2, 4-D; 0, 200 and 500 mg L-1 glutamine and 0, 500 and 1000 mg L-1 asparagine. The embryo number was optimized using the RITA® automatic bioreactors system using a Programmable Logic Controller (PLC) and a Light Dependent Resistor (LDR) varying the immersion frequencies with similar solid and liquid treatments at the same time for comparative purposes. The results showed that interaction between asparagine and glutamine had a statistically significant effect and the largest embryo number was obtained with the higher concentration of the two amino acids, the coefficient of determination (R2) calculated from the validation data for RSM model was 0.92, The use of the RITA® bioreactor had a positive effect on embryo number at 1 min of immersion time and a frequency of 12 times a day comparing with the liquid system but not at others frequencies, possibly because of the physical conditions inside the reactor. Response surface design was an experimental strategy which led to raise the embryo number using asparagine and glutamine as supplement of MS medium in the callus differentiation A. americana L. and using the RITA reactors automatic system was effective to improve the multiplication rate.